Dynamic economic models in discrete time : theory and empirical applications - Ferguson, Brian S.; Lim, G. C. (Guay C.) (London ; New York : Routledge, 2003)
This text introduces the techniques of discrete time modelling starting with first order difference equation models and building up to systems of different equations, covering topics such as non-linear difference equation models and optimization in discrete time models.
Includes bibliographical references (p. [160]-163) and index.
oif 04/05/15
Loan
Keywords: Econometric models; Statics and dynamics (Social sciences); Discrete-time systems